2018
DOI: 10.1002/pds.4386
|View full text |Cite
|
Sign up to set email alerts
|

A systematic assessment of key design and performance characteristics of drug exposure registries requested by the U.S. Food and Drug Administration

Abstract: This study suggests clear objectives, patient accrual/retention efforts, adequate analysis plans, and interim reports contribute to the performance of drug exposure registries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Two studies focusing on more recent imposed registry studies (albeit with inherently shorter follow-up periods than our study and one being a study from the United States) however, found similar results of slow recruitment. 26,27 What we add is that even with longer follow-up periods, recruitment in registries remains poor and that imposed registry studies (a regulatory tool that is likely to have been used more frequently since the new pharmacovigilance legislation) may perform better than nonimposed ones. The exact reasons for poor recruitment were not easily identifiable in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Two studies focusing on more recent imposed registry studies (albeit with inherently shorter follow-up periods than our study and one being a study from the United States) however, found similar results of slow recruitment. 26,27 What we add is that even with longer follow-up periods, recruitment in registries remains poor and that imposed registry studies (a regulatory tool that is likely to have been used more frequently since the new pharmacovigilance legislation) may perform better than nonimposed ones. The exact reasons for poor recruitment were not easily identifiable in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Postauthorization studies based on patient registries are frequently requested to marketing authorization holders by regulatory authorities to support the benefit‐risk monitoring of their licensed drugs . A previous European Medicines Agency (EMA) study examined the characteristics of registries imposed by EMA as a legally binding condition of the marketing authorization .…”
Section: Background and Previous Findingsmentioning
confidence: 99%
“…Postauthorization studies based on patient registries are frequently requested to marketing authorization holders by regulatory authorities to support the benefit-risk monitoring of their licensed drugs. [1][2][3] A previous European Medicines Agency (EMA) study examined the characteristics of registries imposed by EMA as a legally binding condition of the marketing authorization. 1 Of a total of 392 products that received a positive opinion for a marketing authorization from the EMA Committee for Human Medicinal Products between January 1, 2005 and December 31, 2013, 31 registry-based studies had been imposed for 30 products (7.6%).…”
Section: Background and Previous Findingsmentioning
confidence: 99%